Biosorption of Cd2+ Ni2+ and Zn2+ from Contaminated Well Water by Garlic Peel - Soleymani-Bonoti, Fatemeh; Kazemi, Davood; Hajimiri, Ismael; Imani, Alireza (Fine Chemical Engineering, 2024)
The application of garlic peel was investigated as a low-cost biosorbent for Cd2+, Ni2+, Zn2+, and Pb2+ from aqueous solutions in a continuous system. Experiments were carried out in a fixed bed column, and the influence of different flow rates (from 2.0 to 3.3 ml min-1) on the breakthrough was studied. Column data obtained at different conditions were described using the Bohart-Adams, Thomas, and Yan models. The maximum amount of absorption was obtained for a lead ion with the amount of 490.68 mg g-1. The column removed 472.78 and 135.17 mg g-1 of cadmium and nickel ions, respectively, and the minimum value was obtained for zinc ions (55.08 mg g-1). The garlic peel was regenerated and reused two to four times in successive biosorption-desorption cycles. Differential pulse voltammetry (DPV) was used to measure kinetic models for the biosorption of lead and cadmium ions on garlic peels. Using DPV for lead and cadmium ions, the amount of adsorbed material was obtained at 2.58 and 2.23 mg g-1 using the pseudo 1st order equation and this value was obtained at 8.26 and 4.70 mg g-1 using the pseudo 2nd order equation for lead and cadmium ions, respectively. The results show that garlic peel absorbs lead and cadmium ions more than zinc and nickel ions. Because it is made up of several sulfur compounds, sulfur as a soft atom has a stronger interaction with lead and cadmium than other ions.